Researching and analysing business : research methods in practice - Foroudi, Pantea, 1974-; Dennis, Charles (Routledge, 2024)
"Researching and Analysing Business: Research Methods in Practice provides an accessible and practical guide to various data collection and data analysis techniques within management, from both quantitative and qualitative perspectives. This key resource functions as a comprehensive reference tool - covering a broad variety of methodologies - examining both the theory behind them and their application in practice. These include systematic literature review through bibliometric and meta-analysis, secondary vs primary sources, qualitative research vs quantitative research, combining qualitative and quantitative methods, qualitative and quantitative research method approaches, fsQCA, data mining, and sentiment analysis. Chapters are rich in examples, data sets, practical exercises, easy-to-follow slides, and a glossary, which help readers to understand and apply research approaches as well as to assess the strengths and weaknesses of each method. Unique in its practical approach and with insights from active researchers, this book is required and recommended reading for advanced undergraduate and postgraduate students studying research methods as a core module within business and management courses. It is also a useful tool for PhD students and academics within the discipline. Online support materials include PowerPoint slides"--